2021
DOI: 10.1097/scs.0000000000007843
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Orthognathic Surgery: National Analysis of Perioperative Complications

Abstract: cantholysis can be performed to reduce intraorbital pressure and to minimize the risk of vision loss. It is then characterized as a medical emergency, because it can lead to blindness or other life-threatening complications if not treated promptly. [21][22][23] Therefore, the clinical presentation of our patient demanded an early surgical intervention.It is not clear whether SARS-CoV-2 itself is a contributing factor to the pathogenesis in these cases. However, the time of onset and the absence of previous sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Infections were significantly more prevalent in LF1 than BSSO procedures ( P <0.001). On the basis of the studies on adults and children, infections after orthognathic surgery have been reported to range from 1.1% to 33.4% 11,33–36 . A previous multicenter study demonstrated that pediatric patients overall experience infection at a rate of 1.1% after orthognathic surgery 11 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Infections were significantly more prevalent in LF1 than BSSO procedures ( P <0.001). On the basis of the studies on adults and children, infections after orthognathic surgery have been reported to range from 1.1% to 33.4% 11,33–36 . A previous multicenter study demonstrated that pediatric patients overall experience infection at a rate of 1.1% after orthognathic surgery 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Several multi-institutional database studies have shown that performing orthognathic surgery at high-volume centers results in fewer complications, decreased costs, and shorter lengths of stay 1,8 . Although many of these studies analyzed only adult patients, or adult and pediatric populations together, only 1 nationwide study specifically focused on the outcomes of pediatric patients 11 . That study included pediatric patients of all ages from birth through 18 years of age and was able to elucidate the specific risk factors for patients 6 years and younger.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4 The consequences of such complications not only affect the patient's quality of life, resulting in increased morbidity and mortality risks, but can also place a significant financial burden on the patient and healthcare system as well. 2,5,[11][12][13][14] Hence, a focused investigation on these outcomes following orthognathic surgery is warranted to direct future efforts to minimize these costs and complications.…”
Section: Introductionmentioning
confidence: 99%